Deaf children with spoken language bilingualism: Professional guidance to parents. (2nd January 2023) - Wright, Emily; Stojanovik, Vesna; Serratrice, Ludovica
ABSTRACT: 13% of deaf children in the UK use more than one spoken language. Parents of deaf children from bilingual backgrounds must decide whether to communicate with their child using more than one spoken language, with or without a signed language(s) as well. As most deaf children are born to hearing parents with little or no knowledge of deafness, professional guidance received during this decision-making process is critical. This study examined the beliefs of professionals on the ability of a deaf child to acquire two spoken languages and the advice professionals give to parents considering spoken language bilingualism for their deaf child. 108 professionals who work with deaf children in the UK (50 Teachers of the Deaf [ToDs], 47 speech and language therapists [SLTs] and 11 audiologists) completed an online questionnaire between the 24th May 2019 and the 1st July 2019. Most participants believed deaf children can achieve spoken language bilingualism and would advise parents to speak in their home language, regardless of the parents' English proficiency. However, audiologists were 11 times more likely than SLTs to report linguistic confusion, and ToDs at least 11 times more likely than SLTs to report reduced proficiency in English and the home language because of bilingualism. ToDs and SLTs were found to play a key role in bilingual parents' decision-making process. Consequently, there is a need for specific training and interprofessional learning to ensure parents receive consistent evidence-based advice.